2016
DOI: 10.1097/hjh.0000000000000797
|View full text |Cite
|
Sign up to set email alerts
|

Trends in admission blood pressure and stroke outcome in patients with acute stroke and transient ischemic attack in a National Acute Stroke registry

Abstract: Admission SBP in patients with acute stroke and TIA decreased from 2004 to 2010 and may have contributed to the improved outcome in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
0
8
0
4
Order By: Relevance
“…However, several previous studies also demonstrated that increased BP in acute phase may be detrimental to the brain edema and hemorrhage transformation 1820 . So the relationship between early elevation in BP and prognosis remains controversial, some reports suggested that initially high blood pressure was associated with a poor prognosis 2123 , while other study suggested that elevated BP contributed to a more favorable prognosis 8 or did not affect the prognosis 24 .…”
Section: Discussionmentioning
confidence: 97%
“…However, several previous studies also demonstrated that increased BP in acute phase may be detrimental to the brain edema and hemorrhage transformation 1820 . So the relationship between early elevation in BP and prognosis remains controversial, some reports suggested that initially high blood pressure was associated with a poor prognosis 2123 , while other study suggested that elevated BP contributed to a more favorable prognosis 8 or did not affect the prognosis 24 .…”
Section: Discussionmentioning
confidence: 97%
“…2 Pasien stroke akut sering mengalami tekanan darah yang tinggi saat masuk rumah sakit, kondisi ini berhubungan dengan luaran yang buruk seperti perburukan defisit neurologis, stroke rekuren, dan kematian. 3,4 Patologi pada kondisi perdarahan intrakranial menyebabkan timbulnya tekanan intrakaranial serta penurunan tekanan darah sistemik. Hal ini selanjutnya mengakibatkan hipoperfusi dan infark di sekitar jaringan edema, sedangkan peningkatan tekanan darah dapat memperluas daerah edema di area sekitar infark atau perdarahan.…”
Section: Artikel Asli Putri Et Al 2018unclassified
“…Pembahasan Peningkatan tekanan darah saat masuk pada pasien stroke lazim terjadi, baik pada stroke iskemia maupun stroke perdarahan. 4 Hasil penelitian ini menunjukkan adanya hubungan tekanan darah saat masuk dengan mortalitas pasien dengan stroke perdarahan. Hal ini sesuai dengan penelitian yang dilakukan oleh Carlberg et al, bahwa terdapat kecenderungan terjadinya perdarahan berulang saat fase akut stroke pada pasien dengan tekanan darah sistemik yang tinggi.…”
Section: Artikel Asli Putri Et Al 2018unclassified
See 2 more Smart Citations